Efficiency of Combined Use of a Surfactant and the «Lung Opening» Maneuver in the Treatment of Acute Respiratory Distress Syndrome - A. V. Vlasenko; D. A. Ostapchenko; I. N. Pavlyukhin; O. A. Rozenberg (Общая реаниматология, 2007)
The paper discusses whether the «lung opening» maneuver in combination with the endobronchial administration of a pulmonary surfactant can be used in the treatment of patients with acute respiratory distress syndrome (ARDS) of various genesis. The authors outline data of their studies of the separate use of both methods and present the results of successful treatment in a patient with severe concomitant injury and posttraumatic ARDS in the combined use of the «lung opening» maneuver and Surfactant-BL. With intensive care, the combined use of these methods is a more effective way of improving gas exchange as compared with their use alone. Key words: acute respiratory distress syndrome, surfactant-BL, «lung opening» maneuver, combined use of both methods.